Peran Digital Banking dalam Meningkatkan Kinerja Keuangan Perbankan di Indonesia: Sebuah Literature Review - Runa Tania Rinjani; Tania Adelia Putri; Trie Cahya Nania3; Rooswhan Budhi Utomo (Pusat Riset dan Inovasi Nasional, 2026)
Digital transformation has significantly changed the banking industry through the implementation of digital banking as a strategic approach to improve service quality and financial performance. This study aims to analyze the role of digital banking in improving the financial performance of banks in Indonesia using a Systematic Literature Review (SLR) approach. The study employed secondary data from 27 national and international scientific articles collected from Google Scholar, Scopus, ScienceDirect, MDPI, Emerald Insight, and SINTA-indexed journals. The data were analyzed using content analysis by identifying, classifying, and synthesizing previous research findings concerning digital banking implementation, technology adoption factors, and their impacts on banking financial performance. The findings indicate that digital banking generally has a positive effect on banking profitability, particularly on Return on Assets (ROA), Return on Equity (ROE), and operational efficiency as reflected by a lower Operating Expenses to Operating Income (BOPO) ratio. However, these benefits depend on the maturity of digital transformation, organizational digital capabilities, cybersecurity readiness, and the level of customer technology adoption. This study contributes by providing a comprehensive synthesis of the relationship between digital banking and banking financial performance and is expected to serve as a valuable reference for academics, practitioners, and policymakers in supporting the digital transformation of Indonesia's banking industry.